UMUMIY OʻRTA TA’LIMDA „ALPOMISH“ DOSTONINI RAQAMLI TEXNOLOGIYALAR ASOSIDA OʻRGATISH - Allambergenov, H.K. (SCIENCE and SOCIETY, 2024)
The issues of teaching the epic genre based on digital technologies in secondary schools are analysed, scientific and edcational media education resource project in the process of teaching the so called genre is proposed and teaching the events in the epic poem Alpamish with numbers is classified in this article.
Keywords: secondary education; teaching the epic genre; media education resource; numers used in the epic poem “Alpamish”